The analysis of the needs of Free State emergency care practitioners with regard to continuous professional development - Sookram, Bradley Paul (University of the Free State, 2016)
The Health Professions Council of South Africa (HPCSA) recognises and endorses continuing professional development as a means of ensuring best possible practice to the public. The lack of literature regarding continuing professional development for emergency medical care practitioners and the number of non-compliant emergency medical care practitioners, provided evidence for the need to investigate the possible needs faced by emergency medical care practitioners to be compliant to the HPCSA guidelines for continuing professional development in South Africa. The overall goal of the study was to conduct an analysis of the needs of Free State emergency medical care practitioners with regard to continuous professional development. A literature study was done to gain a deeper understanding of continuous professional development with reference to health professionals and specifically emergency medical care practitioners. A questionnaire was compiled considering some barriers that were identified which affected compliance with continuous professional development regulations. The questionnaire was compiled electronically and printed in a hard copy using the Evasys system. The target population was emergency medical care practitioners in the Free State province that were active and registered with the HPCSA. The study revealed that resources, improved communication and access to continuous professional development activities were the main needs of emergency medical care practitioners. Although there were some limitations during this study, it was evident that continuous professional development accreditors, and continuous professional development service providers need to plan, organise and provide information in advance for emergency medical care practitioners to be able to attend continuous professional development activities. Addressing the needs of emergency medical care practitioners with regard to continuous professional development will contribute positively not only towards the workplace but to the community at large.

Die Gesondheidsberoepraad van Suid Afrika, herken en ondersteun voortgesette professionele ontwikkeling, as ‘n manier van die beste moontlike diens aan die publiek. Die gebrek aan literatuur oor voortgesette professionele ontwikkeling vir noodgevalle mediese diens werkers, asook die aantal noodgevalle mediese diens werkers wat nie aan die voortgesette professionele ontwikkeling vereistes voldoen nie, is bewys dat daar ‘n gaping is om moontlike behoeftes van noodgevalle mediese diens werkers te ondersoek, om uit te vind hoekom hulle nie aan die gesondheidsberoepraad van Suid Afrika se riglyne vir voortgesette professionele ontwikkeling voldoen nie. Die doel van die studie was om ‘n analise te doen oor die huidige behoeftes wat noodgevalle diens werkers in die Vrystaat provinsie het in verband met voortgesette professionele ontwikkeling. ‘n Literatuur studie is gedoen om beter insig van voortgesette professionele ontwikkeling te kry met betrekking tot gesondheids werkers en veral noodgevalle mediese diens werkers in die Vrystaat. ‘n Vraelys was saamgestel wat oorwegend hindernisse wat geidentifiseer was in terme van die voldoening van voortgesette professionele ontwikkeling regulasies beinvloed. Die vraelys was elektronies saamgestel met die gebruik van die Evasys sisteem en ‘n harde kopie was gebruik. Die teiken populasie was aktief en geregistreerde noodgevalle mediese diens werkers in die Vrystaat Hierdie studie het aan die lig gebring dat voortgesette professionele ontwikkeling bronne, verbeterde kommunikasie asook toegang tot voortgesette professionele ontwikkeling aktiwiteite die grootste behoeftes vir noodgevalle mediese diens werkers was. Alhoewel daar beperkinge was tydens hierdie studie, het dit geblyk dat geakkrediteerde voortgesette professionele ontwikkeling diens voorsieners en organisasies behoort goed georganiseerde vooruit beplande voortgesette professionele ontwikkeling aktiwiteite te voorsien wat betyds aan noodgevalle mediese diens werkers gekommunikeer word. Deur die voortgesette professionele ontwikkeling behoeftes van noodgevalle mediese diens werkers aan te spreek, sal dit nie net hul werkplek positief beinvloed nie, maar ook die gemeenskap.
Dissertation (M.HPE. (Health Professions Education))--University of the Free State, 2016
Keywords: Continuing professional development; Emergency medical care practitioner; Health Professions Council of South Africa; Continuing professional development regulations; Medical care; Emergency medical personnel